Colonic adenocarcinoma with coexisting tuberculosis: an unusual presentation (Bangladesh Journal of Medical Science, 2016)
Tuberculosis affecting the colon is an uncommon extra-pulmonary form of the disease, and its association with malignancy is highly unusual. A 66-year man presented with lower gastrointestinal bleeding altered bowel habit and significant weight loss. On examination, he had ulcer infiltrative growth in the descending colon, with friable mucosa, bleeds easily on touch. With the diagnosis of carcinoma of the descending colon, he underwent left hemicolectomy. The histopathological examination revealed carcinoma colon with coexisting tuberculosis. The aetiological association between the tuberculosis and colon cancer is a matter of debate. However, the treating surgeon should be aware of this association, to avoid confusion and delay in the management.Bangladesh Journal of Medical Science Vol.15(1) 2016 p.131-134